2013
DOI: 10.4236/health.2013.54097
|View full text |Cite
|
Sign up to set email alerts
|

Approach to perinatal mental health and child abuse prevention in Japanese prefectural health centers

Abstract: The aim of this study was to conduct a nationwide survey in Japan of prefectural health centers, which were responsible for providing guidance to municipalities. The survey was performed in order to clarify the following issues: 1) the current level of support provided by prefectural centers for pre-and post-natal mental health; 2) the structures in place for providing consultation services for an "unwanted pregnancy" and the support available for high-risk cases; and 3) the advice available on postpartum mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…When dealing with maternal depression, it is important to consider the possibility that fathers are not able to fully provide support to mothers and might also need some support. In Japan, there are reports of delayed action regarding perinatal mental health in regional central hospitals that receive pregnant women with psychiatric problems [ 34 ]. Since proper child-rearing is a social responsibility, it is necessary to build better support systems that provide aid to both mothers and fathers after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…When dealing with maternal depression, it is important to consider the possibility that fathers are not able to fully provide support to mothers and might also need some support. In Japan, there are reports of delayed action regarding perinatal mental health in regional central hospitals that receive pregnant women with psychiatric problems [ 34 ]. Since proper child-rearing is a social responsibility, it is necessary to build better support systems that provide aid to both mothers and fathers after childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…During the second and third analyses, two (items 5, 25) and three (items 1,11,22) items were deleted, respectively. At the fourth and final examination, four factors consisting of 14 items remained ( Table 7).…”
Section: Exploratory Factor Analysesmentioning
confidence: 99%
“…The number of reports increases annually, so perinatal health care providers are exploring the tool of contributing to perinatal mental health and child abuse prevention [21,22]. The PBQ could be useful in assessing a mother's emotional feelings toward her baby in clinical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous research has revealed evidence that in Japan, only 15% of hospitals perform maternal depression screening during the perinatal period; furthermore, only 9% of Japanese hospitals administer depression screening during the antenatal period [27]. In contrast, in the United States, 47% of women were screened for maternal depression during their prenatal visits [28].…”
Section: Introductionmentioning
confidence: 99%